Biological functions of cap adjacent RNA methylation in brain - Bellows, Eleanor (2020)
In eukaryotes, mRNA transcripts that are transcribed by RNA polymerase II (RNA pol II) and then subsequently co-transcriptionally modified. One of the co-transcriptional modifications is the addition of the 7-methyl guanine cap to the 5′ end of the RNA. If no further modifications are added to the first two nucleotides, this cap structure is referred to as cap0, and is found in plants and yeast. Additional modifications take place in higher eukaryotes. For example the ribose sugar of the first nucleotide can be methylated at the 2′-O position to give cap1. If this cap1 methylation occurs on an adenosine, the nitrogenous base can be further methylated generating N6,2′-O-dimethyladenosine (m6Am). The function of the m6Am modification is currently unknown. We propose that the m6Am modification may regulate translational processes which underlie neuronal and synaptic function. To understand this, transcripts that have the modification, proteins that bind the modification and evolutionary profile of m6Am will be investigated by preforming Thin Layer Chromatography (TLCs), protein pull downs using RNA oligonucleotides and RNA sequencing and gene orthologue analysis.